Diskurser om defekte kroppe - Whyte, Susan Reynolds (Tidsskriftet Antropologi, 2019)
The notion of discourse is useful in examining the various ways in which impairments of the body are construed. In the last several hundred years of Western history, bodily difference has been the object of Christian charity, pedagogy, medical classification and rehabilitation. The article reviews these shifts in discourse and points to some fundamental assumptions about difference in Euro-American culture. In non-Westem cultures, discourses on bodily anomalies can also be traced. However, discourse analysis of the Foucaultian variety